Atlantoaxial Rotatory Subluxation: A Rare Complication of Craniofacial Surgery. Issue 1 (January 2020) - Patel, Viren; Yang, Robin; Shakir, Sameer; Groves, Mari; Bartlett, Scott P.
Abstract : Introduction: Neck pain is common in the post-operative period after craniofacial procedures. If patients present with neck pain and torticollis, it could be a manifestation of atlantoaxial rotatory subluxlation (AARS), which describes a rare condition in which there is lateral displacement of C1 relative to C2. When this occurs in the post-operative patient, it is termed Grisel syndrome. In this case series, we report on 3 patients diagnosed with Grisel syndrome after a craniofacial procedure. Methods: A retrospective chart review of a single craniofacial surgeon at a pediatric hospital was conducted over the last 3 decades. Demographics, procedures performed, and management strategies of AARS were included for review. Results: Three patients were identified who were diagnosed with Grisel syndrome after a craniofacial procedure and required inpatient cervical traction. All patients presented with torticollis within 1 week of their operation. Conservative management was ineffective, and all 3 patients were admitted for inpatient cervical traction, for an average of 13 days followed by an average of 47 days of outpatient therapy. No patients showed any signs of recurrence after removal of outpatient traction device. Conclusion: Grisel syndrome is a rare, but serious complication of craniofacial procedures. Physicians caring for these patients must have a high degree of suspicion if a patient with a recent craniofacial procedure presents with torticollis. Delaying the initiation of therapy has been shown to lead to higher rates of recurrence and increases the likelihood that patients will require surgical intervention. Abstract : Supplemental Digital Content is available in the text